From Screens to Classrooms: How Cyberbullying Alters University Learning Dynamics - Narges Shahbaz (English Language and Literature in Education Journal, 2025)
Despite growing recognition of cyberbullying as a critical concern, the existing literature primarily focuses on its psychological consequences, with limited exploration of its nuanced effects on academic engagement and social dynamics within higher education contexts, particularly in urban Pakistan. This study aims to examine how cyberbullying influences university learning environments, with an emphasis on female students’ experiences. Adopting a qualitative case study design, data were collected through in-depth, semi-structured interviews with four female undergraduate students who have directly experienced cyberbullying. Thematic analysis revealed three interrelated themes: disruption of victims’ emotional stability and personality traits, deterioration in academic performance, and the complex interplay of parental and peer involvement in coping strategies. Findings indicate that persistent online harassment leads to withdrawal from social and academic participation, decreased motivation, and diminished trust in institutional support systems. Familial support is often limited due to generational and cultural gaps, while close friendships provide the primary emotional buffer. Simultaneously, peers and classmates may exacerbate social exclusion through rumor propagation, highlighting the layered dynamics of social networks in victimization and adaptation processes. The study underscores the necessity of targeted cyber-safety education, structured support mechanisms within universities, and initiatives to enhance parental awareness, providing actionable insights for policymakers, educators, and higher education administrators.